2014
DOI: 10.1002/stem.1826
|View full text |Cite
|
Sign up to set email alerts
|

Pcgf6, a Polycomb Group Protein, Regulates Mesodermal Lineage Differentiation in Murine ESCs and Functions in iPS Reprogramming

Abstract: Polycomb group (PcG) proteins comprise evolutionary conserved factors with essential functions for embryonic development and adult stem cells. PcG proteins constitute two main multiprotein polycomb repressive complexes (PRC1 and PRC2) that operate in a hierarchical manner to silence gene transcription. Functionally distinct PRC1 complexes are defined by Polycomb group RING finger protein (Pcgf) paralogs. So far, six Pcgf paralogs (Pcgf1-6) have been identified as defining components of different PCR1-type comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 69 publications
(97 reference statements)
5
52
0
Order By: Relevance
“…Pcgf6 has been shown to be required to maintain ESC self-renewal by an RNAi screen33 and to be the major Posterior sex combs (Psc) component in Cbx7-bound PRC1 complexes in ESCs34. In a recent study, Pcgf6 was identified as a key regulator of mouse ESC pluripotency and self renewal, iPS reprogramming and mesodermal differentiation35. Knockdown of Pcgf6 was shown to decrease expression of core ESC transcription factors Oct4, Sox2 and Nanog, reduce cellular reprogramming and increase mesodermal and testes-specific gene expression35.…”
mentioning
confidence: 99%
“…Pcgf6 has been shown to be required to maintain ESC self-renewal by an RNAi screen33 and to be the major Posterior sex combs (Psc) component in Cbx7-bound PRC1 complexes in ESCs34. In a recent study, Pcgf6 was identified as a key regulator of mouse ESC pluripotency and self renewal, iPS reprogramming and mesodermal differentiation35. Knockdown of Pcgf6 was shown to decrease expression of core ESC transcription factors Oct4, Sox2 and Nanog, reduce cellular reprogramming and increase mesodermal and testes-specific gene expression35.…”
mentioning
confidence: 99%
“…The genomic binding profile of PCGF6 is similar to TRXG activators and coincides to active chromatin marks. Knock down of Pcgf6 reduced the expression of core pluripotency regulators Oct4, Sox2 and Nanog [338,340]. Conversely Pcgf6 overexpression prevented downregulation of these factors, impaired differentiation and enhanced reprograming [340].…”
Section: Ncprc13 and Ncprc15mentioning
confidence: 97%
“…NcPRC1.6 type complexes are the most abundant ncPRC1s found in mouse ES cells and have a key role in maintaining pluripotency. During neuronal and hematopoietic differentiation, their amount declines [206,338].…”
Section: Ncprc13 and Ncprc15mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, while PRC2 has been shown to facilitate the acquisition of induced pluripotency in different somatic cells (44,101,114,176), G9a/GLP and H3K9 methylation have been instead suggested as a barrier of cellular reprogramming (25,142). Probably, the requirement of PRC2 for an efficient generation of iPSCs relies on its capacity to maintain the silencing of somatic cells transcriptional programs while being involved in repression of pluripotency genes; H3K9 methylation needs instead to be overcome for the reacquisition of pluripotency and an efficient cellular reprogramming (25).…”
Section: Role In Adult Stem Cell Differentiationmentioning
confidence: 99%